Investigating US potato farmers’ preferences for true potato seeds - Vanessa Kambi; Chengyan Yue; Yang Wang; Laura M Shannon (Journal of Agriculture and Food Research, 2025)
This research examines US farmers' preferences for true potato seeds (TPS). An online survey was developed and posted on potato farmers' associations’ websites and newsletters. In total, 56 surveys were completed. Participants were from Minnesota, North Dakota, Wisconsin, Washington, Oregon, Idaho, and New Mexico. Only 13 % of participants used TPS to grow potatoes. The survey data is analyzed by a mixed logit model. The results show that most farmers are not very knowledgeable about true potato seeds. In the current situation, seed type is not essential, and what matters most is the yield and size of potatoes. Participants indicated a willingness to pay $7.24 less for potato seeds associated with a 20 % yield loss compared to those with a 10 % yield loss. Additionally, participants expressed a willingness to pay $7.16 and $3.94 more, respectively, for potato seeds that produce potatoes with compositions of 90 % Grade A potatoes and 10 % Grand B potatoes, and 80 % Grade A potatoes and 20 % Grand B potatoes, as opposed to seeds producing potatoes with a composition of 70 % Grade A potatoes and 30 % Grand B potatoes. Labor input, pesticide/fungicide input, and greenhouses for growing seedlings are important factors to consider when farmers choose between true potato seeds and tuber seeds. Based on our findings, we provided policymakers and stakeholders suggestions for promoting TPS, including holding TPS education, evaluating the need for a TPS certification system, and addressing farmers' priorities.